Preliminary Results of Shake Table Tests of a Typical Museum Display Case Containing an Art Object - Andrea Prota; Martino Zito; Danilo D’Angela; Giuseppe Toscano; Carla Ceraldi; Antimo Fiorillo; Gennaro Magliulo (Advances in Civil Engineering)
The seismic response of freestanding elements is typically extremely critical, and this is associated with a high seismic risk in the case of museum objects and artefacts. This paper reports the preliminary results of an experimental testing campaign aimed at assessing the dynamic properties and the seismic performance of museum objects and artefacts. Shake table tests of a typical museum display case containing a representative art object (vase) are performed. Both dynamic properties and seismic behavior of the specimens were assessed. Tentative damage assessment correlations are developed. The study sheds light on the critical behavior of the tested specimens, stressing the need for further studies towards a more comprehensive assessment of freestanding museum objects and artefacts.